Carlina onopordifolia (Asteraceae) на Східному Поділлі - Мельник, В.І.; Скоропляс, І.О.; Ваколюк, В.Д. (Український ботанічний журнал, 2014)
Рассмотрено географическое распространение и современное состояние популяций редкого вида флоры Европы — Carlina onopordifolia Besser ex Szafer, Kułcz. et Pawł (Asteraceae) на восточном пределе ареала в Центральном (Восточном) Подолье (Винницкая обл.). Проанализированы местообитания и возрастная структура популяций вида в регионе. Предложены рекомендации по улучшению охраны C. onopordifolia на Восточном Подолье. Geographical distribution and current state of populations of a rare species of the European flora, Carlina onopordifolia Besser ex Szafer, Kułcz. et Pawł. (Asteraceae), in the eastern limit of its range in central (eastern) Podillya (Vinnytsia Region) are discussed. Habitats and age structure of the population of this species in the region are analyzed. Recommendations for the improvement of conservation of C. onopordifolia in eastern Podillya are provided.